Multi-omics spatial characteristics of CD8+TRM cells in hepatocellular carcinoma and immunotherapy response prediction - Li, Shipeng; Ma, Ju; Li, Xinqiang; Qiao, Bingbing; Wang, Liancai; Li, Deyu; Zhou, Hua; Xu, Haixu; Cai, Jinzhen (Frontiers in Immunology, 2025)
IntroductionUnderstanding CD8+ tissue-resident memory T cells (TRM) spatial characteristics in hepatocellular carcinoma (HCC) is challenging, and clarifying the spatial feature changes following immunotherapy represents an urgent research gap.MethodsThis study employs a multi-omics approach to analyze the spatial distribution and intercellular interactions of TRM cells in HCC tissues using radiomics, single-cell sequencing, and multiplex immunofluorescence histochemistry (m-IHC).ResultsOur results show that the number of CD8+ TRM cells in HCC increases following immunotherapy. Furthermore, after dividing tumor tissues into the tumor core (TC), invasion margin (IM), and normal tissue (N), a increase in CD8+ TRM cells from the IM to the TC can be observed. Consistent with the results of single-cell sequencing analysis, this change in spatial characteristics may be associated with the interactions between CD8+ TRM cells and CD68+ cells.DiscussionImmunotherapy can modify the spatial characteristics of CD8+ TRM cells via regulating their crosstalk with other immune cells, and the spatial distribution of CD8+ TRM cells in the HCC tumor microenvironment (TME) correlates with immune checkpoint blockade (ICB) therapeutic efficacy. Clarifying the mechanisms of action of immunotherapeutic drugs and developing a non-invasive radiomics model to predict CD8⁺ TRM cell dynamics will facilitate the clinical management of HCC.